Video analysis of technical and tactical behavior in elite climbers - Kotidou, T.; Nani, S.; Papadimitriou, K.; Matsouka, O. (SportMont, 2023)
Climbing performance is considered multifactorial and is characterized by the interaction of technical, tactical, physical, as well as psychological components. However only few studies have investigated these components in elite climbers. The present study aimed to identify elite athletes` technical and tactical behavior regarding the following parameters: a) type of climbing handhold, b) type of climbing foothold and c) torso motion through video analysis. The sample consisted of the final competitions of IFSC Climbing World Cup Kranj (2019). In total, 543 actions were recorded through SportScout video-analysis program, taking into account the parameters a) type of climbing handhold, b) type of climbing foothold and c) torso motion. According to the results, and concerning handholds, it was observed that the majority of the participants selected to use Incuts / Mini-jugs, regardless of whether they performed the next movement with the left or the right hand. Concerning the footholds, it was found that participants mostly selected to use Big footholds regardless of whether they performed the next movement with the left or the right leg. Finally, regarding the correlation between Torso motion and Handholds and the correlation between Torso motion and Footholds, it was found that the majority of the climbers selected to perform movements without Torso twisting. Only the techniques of stepping with the right foot had a significant effect on the motion of the torso (Chi-Square=15.53, p<0.05).In conclusion, the selection of smaller and more difficult handholds and big footholds, as well as the climber`s trunk maintenance towards the wall are highly important performance elements in elite climbers.